AMBIGUITIES IN THE DEFINITION OF QUASI-LOCAL MASS - Woodhouse, N (1987)
For a small surface in a vacuum spacetime, some components of the kinematic twistor are non-zero at the fifth order in the diameter of the surface even though, according to Penrose's modified construction, the leading term in the quasilocal mass mp is sixth order (or higher). This implies that the leading term in mp cannot be defined independent of higher-order terms in the twistor norm.